NIR-II fluorescence microscopic bioimaging for intrahepatic angiography and the early detection of Echinococcus multilocularis microlesions - Alifu, Nuernisha; Yan, Ting; Li, Jun; Zhu, Lijun; Aini, Abudusalamu; Amuti, Siyiti; Wu, Juan; Qi, Wenjing; Guo, Gang; Zhang, Wenbao; Zhang, Xueliang (Frontiers in Bioengineering and Biotechnology, 2023)
Hepatic alveolar echinococcosis (HAE) is caused by the metacestode of Echinococcus multilocularis, which shows characteristics of malignant tumors with high mortality. However, traditional diagnostic imaging methods are still not sufficient for the recognition of HAE microlesions in the early stages. Near-infrared-II (900–1700 nm, NIR-II) fluorescence microscopic imaging (NIR-II-FMI) has shown great potential for biomedical detection. A novel type of negative target imaging method based on NIR-II-FMI with the assistance of indocyanine green (ICG) was explored. Then, NIR-II-FMI was applied to the early detection of HAE for the first time. The negative targeting NIR-II fluorescence imaging of HAE-infected mice at different stages with the assistance of ICG under 808 nm of laser irradiation was obtained. Especially, HAE microlesions at the early stage were detected clearly. Moreover, clear intrahepatic angiography was achieved under the same NIR-II-FMI system.